Dupilumab with concomitant topical corticosteroid treatment in adults with atopic dermatitis with an inadequate response or intolerance to ciclosporin A or when this treatment is medically inadvisable: a placebo‐controlled, randomized phase III clinical trial (LIBERTY AD CAFÉ). (1st May 2018) - de Bruin‐Weller, M.; Thaçi, D.; Smith, C.H.; Reich, K.; Cork, M.J.; Radin, A.; Zhang, Q.; Akinlade, B.; Gadkari, A.; Eckert, L.; Hultsch, T.; Chen, Z.; et al.
Summary: Background: Atopic dermatitis is a chronic inflammatory skin disease that may require systemic therapy. Ciclosporin A (CsA) is a widely used, potent immunosuppressant but it is not effective in all patients with atopic dermatitis, and side‐effects limit its use. Dupilumab, a fully human anti‐interleukin 4 receptor‐alpha monoclonal antibody, inhibits signaling of IL‐4 and IL‐13, key drivers of Type 2/Th2‐mediated inflammation, and is approved in the U.S.A. and the European Union for the treatment of inadequately‐controlled moderate‐to‐severe atopic dermatitis in adults. Objectives: To evaluate efficacy and safety of dupilumab with concomitant topical corticosteroids (TCS) in adults with atopic dermatitis with inadequate response to/intolerance of CsA, or for whom CsA treatment was medically inadvisable. Methods: In this 16‐week, double‐blind, randomized, placebo‐controlled, phase III trial, patients were randomized 1 : 1 : 1 to subcutaneous dupilumab 300 mg weekly (qw) or every 2 weeks (q2w) or placebo. All received concomitant medium‐potency TCS from Week −2 through Week 16; dosage could be tapered if lesions cleared, or stopped for adverse reactions to TCS. Results: In total, 390 patients were screened, 325 were randomized, and 318 completed the trial. Treatment groups had similar baseline characteristics. Significantly more patients in the dupilumab qw + TCS and q2w + TCS groups achieved ≥ 75% improvement from baseline in the Eczema Area and Severity Index at Week 16 vs. the placebo + TCS group (primary end point) (59·1% and 62·6% vs. 29·6%, respectively; P < 0·001 vs. placebo + TCS, both doses). Other clinical outcomes and atopic dermatitis symptoms were significantly improved in the dupilumab qw + TCS and q2w + TCS groups, including pruritus, pain, sleep disturbance, symptoms of anxiety and depression, and quality of life (QoL). Treatment groups had similar overall rates of adverse events (qw + TCS, q2w + TCS and placebo + TCS groups: 69·1%, 72·0% and 69·4%, respectively) and serious adverse events (1·8%, 1·9% and 1·9%, respectively). Conjunctivitis was more frequent with dupilumab + TCS; skin infections were more frequent with placebo + TCS. Conclusions: Dupilumab + TCS significantly improved signs and symptoms of atopic dermatitis and QoL in adults with a history of inadequate response to/intolerance of CsA, or for whom CsA treatment was medically inadvisable. No new safety signals were identified.